2006
DOI: 10.4103/0972-9941.26649
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy: Gaining experience by graded approach

Abstract: Introduction:Laparoscopic adrenalectomy (LA) has become a gold standard in management of most of the adrenal disorders. Though report on the first laparoscopic adrenalectomy dates back to 1992, there is no series of LA reported from India. Starting Feb 2001, a graded approach to LA was undertaken in our center. Till March 2006, a total of 34 laparoscopic adrenalectomies were performed with success.Materials and Methods:The endocrinology department primarily evaluated all patients. Patients were divided into Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In this series of 60 patients, we did not encounter any major complication. Minor complications were observed in three of 60 adrenalectomies performed in 49 patients (5%) that were comparable to reported studies [2,3,24]. Two patients in Group A developed wound infection that was treated with antibiotics while one patient in Group B developed incisional hernia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this series of 60 patients, we did not encounter any major complication. Minor complications were observed in three of 60 adrenalectomies performed in 49 patients (5%) that were comparable to reported studies [2,3,24]. Two patients in Group A developed wound infection that was treated with antibiotics while one patient in Group B developed incisional hernia.…”
Section: Discussionsupporting
confidence: 88%
“…Goitein et al [2] have suggested a minimum of 30 cases to master the technique of LA. A graded approach to achieve expertise also has been suggested [3]. The present study reviewed data of 60 adrenalectomies comparing the change of pattern in indications, size of tumor, duration of surgery, blood loss, morbidity and mortality after fi rst 30 cases.…”
Section: Introductionmentioning
confidence: 98%
“…The technique is described in detail elsewhere. [10] All patients were operated under general anaesthesia. Carboperitoneum was maintained at 12 mm Hg.…”
Section: Methodsmentioning
confidence: 99%
“…Herein we report our experience with 46 laparoscopic adrenalectomies performed for large adrenal masses (> 5 cm) and summarise the operative and postoperative outcomes. [10]…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic evidence of corticotroph tumor growth is the most frequently used criterion for NS diagnosis, either alone 4,[13][14][15][16] , or in combination with increased ACTH levels and/or pigmentation 2,[17][18][19][20][21][22][23][24][25][26][27][28][29] . In the MRI era, early detection of marginal tumor growth (even before clinical manifestations become evident) is possible, giving ground to the concept of replacing the term NS with "corticotroph tumor progression" 14 .…”
Section: Definition Of Nsmentioning
confidence: 99%